2021
DOI: 10.1056/cat.20.0378
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Covid-19 Pandemic by Caring for Our Health Care Workforce as They Care for Our Patients

Abstract: When Santa Clara County in California was identified as an early coronavirus hot spot and health care workers as one of two at-risk populations, it became clear to leaders at Stanford Medicine that their approach would need to prioritize care for those who care for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…The unifying urgency for support underlying the sentiments of our focus group participants was most resounding, regardless of the specific needs identified by respondents. Increasingly, institutions and organizations are starting to share their best practices as it pertains to occupational safety and at-risk faculty [59,62].…”
Section: Discussionmentioning
confidence: 99%
“…The unifying urgency for support underlying the sentiments of our focus group participants was most resounding, regardless of the specific needs identified by respondents. Increasingly, institutions and organizations are starting to share their best practices as it pertains to occupational safety and at-risk faculty [59,62].…”
Section: Discussionmentioning
confidence: 99%
“…-Promoting the health and well-being of health care providers: healthy health care providers are an essential condition for the provision of quality care and services to patients and the population (138). The crisis has shown that their health has often been taken for granted by decision-makers and managers, rather than as a priority requiring well-defined and coherent strategies and actions (139). It is necessary to ensure that the conditions are met to protect them, both in a context of crisis and in routine practice: occupational health and psychological support services; availability of materials and equipment for quality clinical practice; volume and workflow adapted to the complexity of clinical practice, performance criteria freed from a "business" logic; policy that prevents excesses in terms of holiday deprivation and imposed overtime; organizational governance and leadership that reinforce collaboration, trust and transparent communication between professionals and hierarchy.…”
Section: Recommendations and Avenues For Policy And Practicementioning
confidence: 99%
“…The COVID-19 pandemic has caused an enormous burden on the health care system and health care delivery worldwide [1][2][3][4]. As social distancing and quarantining became the new normal, face-to-face clinical visits plummeted, causing the health care system to rapidly shift to telemedicine to leverage their response to the pandemic [5][6][7][8]. Telemedicine created new opportunities for patient care in the context of the COVID-19 pandemic and thus reduced health care disparities [9,10].…”
Section: Introductionmentioning
confidence: 99%